Effect of chicken manure application on cassava biomass and root yields in two agro-ecologies of Zambia - Biratu, G.K.; Elias, E.; Ntawuruhunga, Pheneas; Nhamo, N. (MDPI, 2018)
Fertilizer application is known to increase crop yields and mitigate net soil nutrient mining due to continuous removal. However, smallholder farmers rarely apply adequate fertilizers because of high cost, limited availability and lack of awareness. An experiment was conducted to evaluate the effect of chicken manure on cassava root and biomass yield at Kabangwe and Mansa, two locations representing agroecological zones II and III, respectively, in Zambia. With the aim of exploring alternative soil fertility management for smallholder farmers, the effect of sole chicken manure and mineral fertilizers was evaluated on cassava. The treatments were four levels of chicken manure (0, 1.4, 2.8, 4.2 ton/ha) and a single level of mineral NPK applied at 100N-22P-83K kg/ha as recommended. The design was a Randomized Complete Block (RCBD), with three replications using the improved cassava variety “Mweru” during the 2015/2016 growing season. The results showed significant (p < 0.05) treatment effects on cassava root yields and yield components (fresh and dry root, leaf, stem, and total biomass) at both sites. The highest mean fresh (27.66 ton/ha) and dry root yield (9.55 ton/ha), and total fresh biomass (53.68 ton/ha) and dry biomass (16.12 ton/ha) production were achieved with the application of 4.2 ton/ha of chicken manure. This treatment showed 71% and 81% fresh root yield advantage over the control at Mansa and Kabangwe, respectively. While the marginal rate of return (MRR) was negative for the mineral fertilizer, it was positive for all the chicken manure treatments with the maximum (315%) achieved from the application of 4.2 ton/ha. The study concludes that application of chicken manure significantly increases the yield and biomass production of cassava and is economically efficient.